Light emitting diode color rendition properties - Hood, Sean (Kansas State University, 2013)
This paper discusses the color rendition capabilities of light emitting diodes (LEDs) and their relationship with the current standard for color rendition quality. The current standard for judging light source color rendering properties, known as the color rendering index (CRI), has come under heavy scrutiny in recent years with the introduction of LED in commercial lighting applications. LEDs, depending on construction type, have highly structured spectral distributions which do not scale well under the color rendering index; moreover, CRI for LEDs has become disjointed with the subjective measurement of human color preference. Unfortunately, given the multidimensional nature of color, an all-encompassing scale with a single rated value for color rendition capabilities of a light source has proven difficult to establish. An analysis on the human visual system is first discussed, establishing how the visual system first detects color in the eye and subsequently encodes that color information through a color-opponent process, formulating conscious color appearance. The formation of color appearance leads into a discussion on human color vision and the creation of three dimensional color space, which is subsequently used for the measurement of color fidelity (CRI) of consumer light sources. An overview of how LED lamps create light and color is then discussed, showing that the highly structured spectral distribution of LED lamps is often the cause of discrepancy within the CRI system. Existing alternatives to the CRI system are then compared and contrasted to each other, and the existing CRI system. A final color preference study was conducted where four LED lamps where compared to a reference lamp of equal correlated color temperature. Observers were asked to rate the various test lamps against the reference lamp in terms of vividness, naturalness, overall preference, and individual color preference. It was found that no significant difference was found between the first three dimensions measured but significant trend lines existed for the preference of individual colors when illuminated by either LED lamps or the reference source. Recommendations are then made for how the lighting industry could move forward in terms of color metrics.
Keywords: Light Emitting Diode; Color Render Preference; Architectural engineering (0462); Engineering (0537)